PROBLEMS OF PHYSICAL EDUCATION OF STUDENTS IN HIGHER EDUCATIONAL INSTITUTIONS - Shokirov Kamol Fazlievich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. At the moment, the shortcomings in the University system of physical education are clear. Monitoring shows a low level of health of students, low interest in physical education, low level of physical fitness and low productivity. In our work we have considered the main problems of physical education in universities, as well as ways to solve them.